A Postcolonial Woman's Encounter with Moses and Miriam - Song, Angeline M.G. (Postcolonialism and Religions, 2015)
This book is grounded in a theorization of the author's personal story including growing up as a female adoptee of a single parent in a patriarchal context, and current material context as an immigrant in New Zealand